2012
DOI: 10.1016/j.aprim.2011.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Análisis del uso racional de antihipertensivos en la región de Murcia

Abstract: The use of antihypertensive drugs in Murcia is less than in the rest of Spain. Therefore, this may be due to a problem of under treatment of this illness or other cardiovascular illnesses in the region. A greater use of ARB in Murcia and a lower use of ACEI was observed in Murcia. The differences found suggest that further studies are required to clarify their origins and causes, with the objective of achieving a more rational and efficient use of these drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…They all occupy the shady sides of the large mountains in the Region of Murcia. In agreement with Alcaraz Ariza et al [19], it has been observed that the species inhabits soils that naturally have higher edaphic moisture.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…They all occupy the shady sides of the large mountains in the Region of Murcia. In agreement with Alcaraz Ariza et al [19], it has been observed that the species inhabits soils that naturally have higher edaphic moisture.…”
Section: Resultssupporting
confidence: 90%
“…Regarding its distribution on the Iberian Peninsula, a sketch of its distribution in the Spanish province of Guadalajara was already made in 1985 [18]. In the Region of Murcia, the gall oak, due to its water requirements, can be found in places where soil moisture or precipitation is higher than in the rest of the region, such as riverbeds and wetter mountain areas [19].…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics are in consonance with the distribution of AHT, which affects more than 60% of people over the age of 60 years in developed countries [ 15 ]. The distribution of antihypertensive treatments, with a predominance of ACE inhibitors, ARA-II, and diuretics used in combination, is very similar to the findings reported by other studies conducted in Spain in recent years [ 16 , 17 ]; i.e., to the effect that up to one in three antihypertensive drugs corresponds to ACE inhibitors, and up to one in four corresponds to a diuretic or diuretics used in combination regimens. Our results showed a high proportion, as much as 19.0%, of participants who reported some adverse effect linked to their antihypertensive medication.…”
Section: Discussionsupporting
confidence: 85%